Kegiatan Cyber Public Relations Yayasan Daarut-Tauhiid pada Media Sosial Instagram - Mubarok, Muhammad Fahmil; Sumadiria, A.S. Haris (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This study aims to determine the Daarut-Tauhiid Foundation's cyber public relations activities in managing the Instagram account @daarut.tauhiid through the stages; Sharing (Share), Optimizing (Optimize), Manage (Manage), and Engage (Engage). This study uses a qualitative descriptive method, and the paradigm of constructivism. Collecting data in this study using observation techniques, in-depth interviews, and documentation. The results in this study indicate that the management of the @daarut.tauhiid Instagram account has four stages, namely: 1) (Share), namely the Daarut-Tauhiid Foundation utilizes the Instagram social media platform as a medium of information, communication and Islamic da'wah. 2) (Optimize), namely the Daarut-Tauhiid Foundation's efforts to maximize the delivery of information by producing various types of content, and improving the quality of content. 3) (Manage), namely the Daarut-Tauhiid Foundation creates content and uses Instagram features. 4) (Engage), namely the Daarut-Tauhiid Foundation's efforts to involve the public within the Daarut-Tauhiid Foundation and the community that is the target of content creation.